Post a New Question


posted by on .

solve for
10/x^2-2x + 4/x = 5/x-2

3x/x+1 + 6/2x = 7/x

8(x-1)/x^2-4 = 4/x-2

check for any extraneous solutions! thanks!

  • alg2 - ,

    I'll do one, and you try the others. If you get stuck, come on back.

    10/(x^2-2x) + 4/x = 5/(x-2)

    x^2-2x = x(x-2), so that's the LCD. Multiply through to get

    10 + 4(x-2) = 5x
    10 + 4x - 8 = 5x
    x = 2
    Unfortunately, the original equation has (x-2) in the denominator, so it is undefined there. No solution.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question